The role of proper treatment of maxillary sinusitis in the healing of persistent oroantral fistula - David B. Kamadjaja (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Oroantral communication (OAC) is one of the possible complications after extraction of the upper teeth. If not identified and treated properly, a large OAC may develop into oroantral fistula (OAF) which means that there is a permanent epithelium-lined communication between antrum and oral cavity. Such fistulas may cause ingress of microorganism from oral cavity into the antrum leading to maxillary sinusitis. Oroantral fistula usually persists if the infection in the maxillary antrum is not eliminated. Therefore, treatment of oroantral fistula should include management of maxillary sinusitis in which surgical closure of oroantral fistula should be done only when the sinusitis has been cured. Purpose: This case report emphasizes on the importance of proper management of maxillary sinusitis in the healing of oroantral fistula. Case: A case of an oroantral fistula following removal of upper left third molar is presented. As the maxillary sinusitis was not identified pre-operatively, two surgical procedures to close the fistula had ended up in dehiscence. Case management: The diagnosis of maxillary sinusitis was finally made and the sinusitis subsequently treated with combination of trans-alveolar sinus wash out, insertion of an acrylic splint, and two series of nasal and sinus physiotherapy procedures. The size of the defect decreased gradually during the treatment of the sinusitis and finally closed up without any further surgical intervention. Conclusion: This case report points out that it is important to detect intraoperatively an antral perforation after any surgery of the maxillary teeth and to close any oroantral communication as early as possible and that it is important to treat properly any pre-existing maxillary sinusitis before any surgical method is done to close the fistula.